Profecia, Glossolalia e Entusiasmo Carismático no Cristianismo Primitivo do Primeiro Século: Uma Análise Exegética de 1Coríntios 14,1-25. - Formicki, Leandro (2013)
This exegetical study aims to analyze the phenomenon of prophecy and glossolalia in early Christianity from the First Letter to the Corinthians. For this, we review a few discussions about exegetical text. The Christian movement emerged as a Jewish sect, but matured in the Greco-Roman environment, being deeply affected by Western culture and traditions. On the one hand, suffered the influences of ancient Israelite traditions and Judaism of the Second Temple, and on the other, suffered the influences of Greco-Roman traditions, although to a lesser degree. Thus, this research shows that the prophecy and glossolalia in 1st Corinthians are ecstatic phenomena, in which context is the nearest Jewish apocalyptic mysticism.